Workplace violence, job satisfaction, burnout, perceived organisational support and their effects on turnover intention among Chinese nurses in tertiary hospitals: a cross-sectional study. Issue 6 (9th June 2018) - Liu, Wenhui; Zhao, Shihong; Shi, Lei; Zhang, Zhong; Liu, Xinyan; Li, Li; Duan, Xiaojian; Li, Guoqiang; Lou, Fengge; Jia, Xiaoli; Fan, Lihua; Sun, Tao; et al.
Abstract : Objectives: Our aims were to assess the relationship between workplace violence, job satisfaction, burnout, organisational support and turnover intention, and to explore factors associated with turnover intention among nurses in Chinese tertiary hospitals. Methods: The purposive sampling method was used to collect data from August 2016 through January 2017. A total of 1761 nurses from 9 public tertiary hospitals in 4 provinces (municipalities) located in eastern (Beijing), central (Heilongjiang, Anhui) and western (Shaanxi) regions of China completed the questionnaires (effective response rate=85.20%). A cross-sectional study was conducted using the Workplace Violence Scale, Chinese Maslach Burnout Inventory General Survey, Minnesota Job Satisfaction Questionnaire Revised Short Version, Perceived Organizational Support-Simplified Version Scale and Turnover Intention Scale. Results: A total of 1216 of 1706 (69.1%) participants had high turnover intention. During the previous 12 months, the prevalence of physical violence and psychological violence towards nurses was 9.60% and 59.64%, respectively. As expected, the level of turnover intention was negatively correlated with participants' scores on job satisfaction (r=−0.367, p<0.001) and perceived organisational support (r=−0.379, p<0.001), respectively. Burnout was positively associated with turnover intention (r=0.444, p<0.001). Workplace violence was positively associated with turnover intention (β=0.035, p<0.001) in linear regression analysis. The total effect (β=0.53) of workplace violence on turnover intention comprised its direct effect (β=0.36) and its indirect effect (β=0.17). Conclusions: Perceived organisational support served as a mediator between workplace violence, job satisfaction, burnout and turnover intention, and it had a significantly negative impact on turnover intention. Therefore, nursing managers should understand the importance of the organisation's support and establish a reasonable incentive system to decrease turnover intention.